Range of motion after total knee arthroplasty in hemophilic arthropathy - Kubeš, Radovan (BMC Musculoskelet Disord, 2018)
BACKGROUND: Outcomes of total knee replacement in cases of hemophilic patients are worse than in patients who undergo operations due to osteoarthritis. Previous publications have reported varying rates of complications in hemophilic patients, such as infection and an unsatisfactory range of motion, which have influenced the survival of prostheses. Our retrospective study evaluated the data of hemophilic patients regarding changes in the development of the range of motion. METHODS: The data and clinical outcomes of 72 total knee replacements in 45 patients with hemophilia types A and B were reviewed retrospectively. Patients were operated between 1998 and 2013. All of the patients were systematically followed up to record the range of motion and other parameters before and after surgery. RESULTS: The mean preoperative flexion contracture was 17° ± 11° (range, 0°-40°), and it was 7° ± 12° (range, 0°-60°) postoperatively. The mean flexion of the knee was 73° ± 30° (range, 5°-135°) before the operation and 80° ± 19° (range, 30°-110°) at the last follow-up. The mean range of motion was 56° ± 34° (range, 0°-130°) before the operation and 73° ± 24° (range, 10°-110°) at the last follow-up. CONCLUSIONS: Statistical analysis suggested that the range of motion could be improved until the 9th postoperative week. The patient should be operated on until the flexion contracture reaches 22° to obtain a contracture < 15° postoperatively or until the contracture reaches 12° to obtain less than 5°. The operation generally does not change the flexion of the knee in cases of hemophilic patients, but it reduces the flexion contracture and therefore improves the range.